Domesticity All Dressed-up: Gender in Antebellum Politics and Culture - van Riemsdijk, Tatiana (Labour / Le Travail, 1998)
The article review and comments on Elizabeth Varon's "We Mean to be Counted: White Women and Politics in Antebellum Virginia" (1998) and Lora Romero's "Home Fronts: Domesticity and its Critics in the Antebellum United States" (1997).